KATA TABU YANG TERKAIT DENGAN GENDER DALAM BAHASA INGGRIS DAN BAHASA KARO: SUATU ANALISIS KONTRASTIF - SEMBIRING, ANGGUN NOPIA BR; RATTU, JULTJE A.J.; PAMANTUNG, RINA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â This research entitled â€œTaboo Word Related to Gender in English and Karo Language: A Contrastive Analysisâ€. The objectives of this research is to identify and classify the kinds of taboo words related to gender in English and Karo language and to analyze the difference of both languages. This research used descriptive method, which takes three steps to finish this research. In preparation, the writer reads some books and journals abouts taboo words and gender to find the relevan theory. The data of the kinds of taboo words related to gender in English were collected by American Pie movie and skripsi, while taboo words related to gender in Karo language were taken from interviewing to 10 informants. The data about taboo words related to gender in English and Karo language that have been collected, then classified, analyzed and described by using the theory of Wardaughâ€™s (1986), then the data of both languages were contrasted by using Ladoâ€™s theory (1975). The result of this reseach showed that there are four kinds of taboo word related to gender in English and Karo language, namely taboo word related to sexs, part of body, animals and excretions. In Karo language showed that, there are anothers taboo words which arenâ€™t included in Wardaughâ€™s theory, which related to kinship and ancestor. Â Â Keywords: Taboo Words, Gender, English and Karo Language, Contrastive Analysis